Analisis Kepuasan Kerja Pegawai Pada Inspektorat Kabupaten Mandailing Natal - Nora, Agustalinda; Batubara, Hery Dia Anata; Sari, Diana; Maharani, Fithra; Pane, Pertama Yul Asmara; Batubara, Rizky Husada (JUEB : Jurnal Ekonomi dan Bisnis, 2024)
The purpose of this study was to determine the level of employee job satisfaction at the Mandailing Natal Regency Inspectorate Office. The method used in this research is descriptive method with quantitative approach and verification method. The types and sources of data for this research are primary and secondary data. The data collection techniques used are interviews, observations and questionnaires. From the results of the discussion, it is concluded that the category of job satisfaction level of Mandailing Natal Regency Inspectorate employees is "Satisfied" with an average score of 3.6 respondents' answers. Of all the existing indicators, it can be concluded that the highest score is obtained by the third indicator, namely working conditions with an average score of 3.8.  Meanwhile, the lowest score was obtained in the first indicator, namely salary with an average score of 3.4. This low score is important to be discussed for the Mandailing Natal Regency Inspectorate because salary is the main basic thing for someone to do work. Of the 7 (seven) indicators used, the average score value is obtained, namely the first indicator obtained an average score of 3.4 (Satisfied), the second and fourth indicators obtained an average score of 3.6 (satisfied), the third indicator obtained an average score of 3.8 this score is also included in the satisfied category, the fifth and seventh indicators obtained an average score of 3.7 (satisfied). And the sixth indicator obtained an average score of 3.5 (satisfied).